2014
DOI: 10.5194/tc-8-2047-2014
|View full text |Cite
|
Sign up to set email alerts
|

Glacier-like forms on Mars

Abstract: Abstract. More than 1300 glacier-like forms (GLFs) are located in Mars' mid-latitudes. These GLFs are predominantly composed of ice-dust mixtures and are visually similar to terrestrial valley glaciers, showing signs of downhill viscous deformation and an expanded former extent. However, several fundamental aspects of their behavior are virtually unknown, including temporal and spatial variations in mass balance, ice motion, landscape erosion and deposition, and hydrology. Here, we investigate the physical gla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 62 publications
5
53
0
Order By: Relevance
“…Although water ice is not presently stable across much of Mars' mid-latitudes (Mellon and Jakosky, 1995;Mellon et al, 2004), evidence of pervasive ice-rich landforms between 30 and 60 o latitude has been presented (Sharp, 1973;Squyres, 1978Squyres, , 1979Lucchitta, 1984;Mangold, 2003;Levy et al, 2007;Baker et al, 2010;Dickson et al, 2010;Head et al, 2010, Souness et al, 2012Hubbard et al, 2014;Brough et al, 2016;Sinha and Murty, 2015). Based on evidence from the Shallow Radar (SHARAD) instrument on board the Mars Reconnaissance Orbiter (MRO), the composition of these ice-rich deposits is consistent with water ice (Holt et al, 2008;Plaut et al, 2009), and their surface morphologies are indicative of viscous flow of that ice (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although water ice is not presently stable across much of Mars' mid-latitudes (Mellon and Jakosky, 1995;Mellon et al, 2004), evidence of pervasive ice-rich landforms between 30 and 60 o latitude has been presented (Sharp, 1973;Squyres, 1978Squyres, , 1979Lucchitta, 1984;Mangold, 2003;Levy et al, 2007;Baker et al, 2010;Dickson et al, 2010;Head et al, 2010, Souness et al, 2012Hubbard et al, 2014;Brough et al, 2016;Sinha and Murty, 2015). Based on evidence from the Shallow Radar (SHARAD) instrument on board the Mars Reconnaissance Orbiter (MRO), the composition of these ice-rich deposits is consistent with water ice (Holt et al, 2008;Plaut et al, 2009), and their surface morphologies are indicative of viscous flow of that ice (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the steepness of some SGLFs, the rate of resurfacing caused by internal deformation within them should be low, because we expect SGLFs to be thin (much thinner than VFFs generally) and this implies limited ice-flow velocity. For instance, a tentative glaciological model (Karlsson et al, 2015), with its optimised plastic yield stress of 22 kPa and typical observed surface slope angles (15-30 • , Figures 5c and supporting information, S38-S39), yields a ball-park estimate for the thickness of SGLFs of only 11-24 m, which is consistent with their often concave surfaces (Hubbard et al, 2014). Although this estimate does not include a calculation of ice-flow velocity (e.g., using Glen's flow law, Cuffey & Paterson, 2010) because the ice composition/rheology and temperature history are both uncertain, it points towards very subdued ice flow and limited reworking of their impact craters.…”
Section: Robustness Of Model Agesmentioning
confidence: 60%
“…However, such a retreat leaves glacial lineations or recessional moraines (Dowdeswell et al, 2016), which are not observed within Reuyl (Figure 4). (3) No glacier-related landforms, such as viscous flow features, lobate debris aprons with moats (Hauber et al, 2008), lineated valley fills, valley-parallel lineations (Kress et al, 2006), drumlins, moraines (Burr et al, 2009), or other glacierlike forms (Hubbard et al, 2014) are observed within Reuyl. Such a lack of typical glacial landforms leads us to eliminate an esker origin for SR within Reuyl (Burr et al, 2009;DiBiase et al, 2013;Lefort et al, 2012).…”
Section: Srsmentioning
confidence: 99%